L’affezione visuale del cinema di Carmelo Bene: Estratto del saggio: G. Raciti, “Aprire i corpi come affezione visuale del cinema di Carmelo Bene” - Raciti, Giulia (Scenari, 2021)
Despite iconoclastic vocation to blind the vision in the name of a tension to the dépense attributable to Bataille, it is undeniable that the cinema of Carmelo Bene is baroque and figurative, as highlighted by Maurizio Grande, and presents various aspects related to the Pictorial Turn trend. Indeed, with the present report we will continue to isolate the innumerable pictorial citations inserted, even at a subliminal level, in the filmic diegesis of Bene, which we will analyze through an approach to Visual Studies, with particular reference to Warburg and Didi-Hubbermann. From such an investigation we aim to highlight the contemporary relevance of Bene’s cinema, which used avant-garde and new wave tactics to reflect meta-linguistically on the status of the filmic image.